Electron microscopic features of thyroid parafollicular cells in rats after a 60-day administration of Tartrazine and Mexidol ® - Luzin, Vladyslav I.; Vitaly N. Morozov (Saratov Medical Journal, 2023)
Objective: to identify the effect of a 60-day isolated tartrazine administration, as well as in combination with the Mexidol ®, on the structural features of parafollicular cells in the thyroid of rats at the electron microscope level. Materials and Methods. We distributed 30 white male rats weighing 200–210 g among five groups of equal sizes. Group I served as a control. Groups II and III included rats receiving tartrazine at concentrations of 750 and 1,500 mg/kg, respectively, for 60 days. Groups IV and V comprised animals under similar conditions, but with Mexidol ® administered at a dose of 50 mg/kg. Qualitative changes in parafollicular cells were examined using electron microscopy, while quantitative changes were assessed via morphometry. Results. After exposure to tartrazine, fine-grained or fibrous contents were detected in cisternae of the rough endoplasmic reticulum, and in some mitochondria, there were areas of destroyed matrix. The euchromatin to heterochromatin areas ratio decreased in groups II and III by 5.7% and 56.9%, respectively, and the diameter of secretory granules did so by 12.3% and 19%, correspondingly, vs. the control (Group I). However, the above ratio in Group V increased by 79.6%, and the diameter of secretory granules did so by 8.2% and 6.5% in Groups IV and V, respectively, compared with animals of Groups II and III. Conclusion. Administration of tartrazine in different doses for 60 days triggered dose-dependent qualitative and quantitative changes in the ultrastructure of parafollicular cells, while administration of the Mexidol ® against this background caused a reduction in the severity of changes.